Can the motor vehicle manufacturing industry be sustainable? Exploring the relationships between profitability, the green economy and environmental sustainability in South Africa. (2017) - Mutumi, Prue Portia Jacqueline; Simatele, Danny
This paper discusses the applicability of environmental sustainability initiatives within the motor vehicle manufacturing industry in South Africa. Sustainability principles remain contested because of divergent interpretations although several studies have suggested the concept refers to using resources to meet intergenerational societal needs, whilst ensuring ecological conservation. The South African manufacturing industry which houses vehicle manufacturing has been identified as a suitable industry for pursuing sustainability principles, largely because vehicle industries yield resources and power that can facilitate mainstreaming a green agenda under the 'green growth path' the country has adopted. Using secondary and primary data collected through an extensive literature review and a pilot study, this paper discusses how the automotive industry can align itself with environmental sustainability principles within regulatory structures on a national, regional and global scale. This has been analysed vis-à-vis current debate on the relationship between the 'green economy' and sustainable development, emphasising on environmental sustainability.